Nonlinear dynamics of a Liénard delayed-feedback optoelectronic oscillator - Romeira, B.; Figueiredo, J.; Ironside, Charlie; Seunarine, K.; Javaloyes, J. (2011)
We present an optoelectronic oscillator (OEO) that is capable of generating complex and rich dynamics including stable periodic oscillations and broadband chaos. The OEO under analysis here is based on a resonant tunneling diode (RTD) oscillator driving a laser diode and a time-delayed feedback loop. The RTD based OEO is well described as a a Liénard oscillator with delayed-feedback. When subjected to external perturbation, the RTD-OEO generates periodic and chaotic states that are controlled by the delayed-feedback loop characteristics. The implemented numerical Liénard optoelectronic oscillator provides a simple way to study time-delayed dynamical systems containing negative resistance oscillators. © 2011 IEEE.